Comparative Evaluation of Appearance and Nutritional Qualities of 57 Tomato (Solanum lycopersicum L.) Accessions - Yiwen Yang; Jinghong Luo; Yueming Tang; Zhi Li; Liang Yang; Jia Gao (Horticulturae, 2025)
This study aims to comparatively analyze and evaluate the postharvest quality of tomatoes, and to further screen and utilize the excellent tomato germplasm resources. Correlation analysis, principal component analysis (PCA), and cluster analysis were performed on 18 appearance and nutritional quality indicators of 57 tomato F1 hybrids (labeled accession 1# to 57#). The results show that the variation coefficients of the tested quality indicators among tomato accessions ranged from 3.77% to 42.92%. Among them, 11 indicators had variation coefficients greater than 10%. The soluble protein content had the highest variation coefficient. Six principal components were extracted through PCA, accounting for 78.696% of the variability. The appearance indicators (size, single fruit weight, and a* value) and soluble solid content played key roles in tomato quality evaluation. According to the calculated comprehensive scores, the top 10 accessions with superior overall quality were selected from the tested tomato accessions. Cluster analysis divided the 57 tomato accessions into two major groups and seven subgroups. Notably, accession 6# showed the best flavor and nutritional quality, which could be a focus for future tomato breeding. These results provide a theoretical basis for comprehensive evaluation of tomato and quality improvement in tomato breeding.